Efektivitas Pelaksanaan Pembelajaran Matematika di SMK Negeri 6 Padang - Elsi Retriani; Nita Putri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the effectiveness of mathematics learning implementation at SMK Negeri 6 Padang, reviewed from three main stages: preliminary activities, core activities, and closing activities. The method used is a combination of qualitative and quantitative approaches. Data collection techniques include participatory observation, in-depth interviews with teachers and students, as well as documentation. The research instruments consist of observation guidelines, interview guidelines, and questionnaires. The results of the study indicate that during the preliminary stage, teachers have conducted apperception but have not yet optimally implemented diagnostic assessments. The core activities are still dominated by conventional methods without the integration of contextual approaches or educational technology. The closing activities fully reflect in-depth reflection and are accompanied by adequate follow-up learning.Overall, the effectiveness of mathematics learning implementation at SMK Negeri 6 Padang is 77.77% in grade X and 77.77% in grade XI, which falls into the effective category. It is necessary to develop innovative learning strategies, utilize technology-based learning media, and enhance student engagement to make the learning process more active, meaningful, and aligned with the needs of vocational education.